Family history of pain and risk of musculoskeletal pain in children and adolescents: a systematic review and meta-analysis - Dario, AB; Kamper, SJ; O'Keeffe, M; Zadro, J; Lee, H; Wolfenden, L; Williams, CM (Lippincott, Williams and Wilkins, 2019)
Emerging evidence suggests that MSK should be viewed from a biopsychosocial perspective and consider the influence of family factors. We conducted a review with meta-analysis to provide summary estimates of effect of family history of pain on childhood MSK pain, and explore whether specific family pain factors influence the strength of the association (PROSPERO CRD42018090130). Included studies reported associations between family history of pain and non-specific MSK pain in children (age <19 years). The outcome of interest was MSK pain in children. We assessed the methodological quality using a modified version of the Quality in Prognosis Studies instrument, and quality of evidence for the main analyses using the GRADE criteria. After screening of 7281 titles; six longitudinal and 23 cross-sectional studies were included. Moderate quality evidence from five longitudinal studies (n=42131) showed that children with family history of MSK pain had 58% increased odds of experiencing MSK pain themselves (OR 1.58, 95% CI 1.20 to 2.09). Moderate quality evidence from 18 cross-sectional studies (n=17274) supported this finding (OR 2.02, 95% 1.69 to 2.42). Subgroup analyses showed that the relationship was robust regardless of whether a child’s mother, father or sibling experienced pain. Odds were higher when both parents reported pain compared to one [(mother OR=1.61; father OR=1.59); both parents OR=2.0]. Our findings show moderate quality evidence that children with a family history of pain are at higher risk of experiencing MSK pain. Understanding the mechanism by which this occurs\ would inform prevention and treatment efforts.